The Remission Effects of First Injection of Sclerotherapy for Pediatric Rectal Prolapse: A Systematic Review and Meta-Analysis - Zhou, Weimo; Shi, Yingzuo; Zhang, Ming; Li, Li (Frontiers in Surgery, 2022)
Background Pediatric rectal prolapse is a common issue in clinical practice. Among various managements, sclerotherapy is an important method to successfully treat pediatric rectal prolapse, especially for the first injection. The knowledge of the first injection of sclerotherapy can be revealed by a systemic review and meta-analysis of randomized clinical trials. Methods We performed a systematic search and a meta-analysis for the retrospective clinical studies of sclerotherapy in pediatric rectal prolapse. The comparison between remission and recurrence after the first injection of sclerotherapy was performed to find if the first injection of sclerotherapy can treat rectal prolapse completely. After a restricted selection, 17 studies involving 1,091 pediatric rectal prolapse subjects with sclerotherapy were enrolled in a variety of classifications of injection agents. The focused outcome was to check whether the first injection of sclerotherapy can achieve a remission status. The meta-analysis was performed by Review Manager 5.4. Results Among the subjects receiving sclerotherapy, the meta-analysis favors the remission status after receiving the first injection of sclerotherapy. The meta-analysis results showed significant remission tests for the overall effect and significant heterogeneities in odds ratio and the fixed-effects model. The significant therapeutic effects remained, however, even after testing in the relative risk and the random-effects model. Conclusions Despite significant heterogeneity and relatively low quality of evidence, the first injection of sclerotherapy may conceivably demonstrate therapeutic effects to help the patients of pediatric rectal prolapse achieve a remission status.